Barbara Noskes "Huilen met de wolven" gesitueerd in het kader van de milieu-ethiek. - Geeraerts, Kurt (Brussel : VUB, 1993)
Aanwinst van De Batselier, Norbert
Licentiaatsverhandeling VUB
Nederlands
Thesis
Keywords: milieu